Biological sex, microglial signaling pathways, and radiation exposure shape cortical proteomic profiles and behavior in mice - Alexandra O. Strohm; Sadie Oldfield; Eric Hernady; Carl J. Johnston; Brian Marples; M. Kerry O'Banion; Ania K. Majewska (Brain, Behavior, & Immunity - Health)
Patients receiving cranial radiation therapy experience tissue damage and cognitive deficits that severely decrease their quality of life. Experiments in rodent models show that these adverse neurological effects are in part due to functional changes in microglia, the resident immune cells of the central nervous system. Increasing evidence suggests that experimental manipulation of microglial signaling can regulate radiation-induced changes in the brain and behavior. Furthermore, many studies show sex-dependent neurological effects of radiation exposure. Despite this, few studies have used both males and females to explore how sex and microglial function interact to influence radiation effects on the brain. Here, we used a system levels approach to examine how deficiencies in purinergic and fractalkine signaling, two important microglial signaling pathways, impact brain proteomic and behavioral profiles in irradiated and control male and female mice. We performed a comprehensive analysis of the cortical proteomes from irradiated and control C57BL/6J, P2Y12−/−, and CX3CR1−/− mice of both sexes using multiple bioinformatics methods. We identified distinct proteins and biological processes, as well as behavioral profiles, regulated by sex, genotype, radiation exposure, and their interactions. Disrupting microglial signaling, had the greatest impact on proteomic expression, with CX3CR1−/− mice showing the most distinct proteomic profile characterized by upregulation of CX3CL1. Surprisingly, radiation exposure caused relatively smaller proteomic changes in glial and synaptic proteins, including Rgs10, Crybb1, C1qa, and Hexb. While we observed some radiation effects on locomotor behavior, biological sex as well as loss of P2Y12 and CX3CR1 signaling had a stronger influence on locomotor outcomes in our model. Lastly, loss of P2Y12 and CX3CR1 strongly regulated exploratory behaviors. Overall, our findings provide novel insights into the molecular pathways and proteins that are linked to P2Y12 and CX3CR1 signaling, biological sex, radiation exposure, and their interactions.